Do the Rules of Europe’s Leading Institutional Arbitration Courts and the UNCITRAL Arbitration Rules Need to Be Revised? Assessment from the Perspective of 2023 - Asłanowicz, Marcin (Review of European and Comparative Law, 2023)
While some issues (e.g. the principles of service, the expedited procedure for resolving cases and the admissibility of securing a claim before initiating proceedings) are regulated in a manner that satisfies the requirements of 2023, other issues (e.g. the rules of holding remote hearings or the consequences of failing to meet deadlines in arbitration, in particular the deadlines for issuing an award) would require a numer of modifications and improvements. This suggests that a postulate should be presented for a broader discussion within the community – both in Poland and abroad – on the shape of the regulations in this area that would be the most comfortable for the parties to the proceedings, the arbitral tribunals and the arbitral institutions, while respecting the basic (universal) arbitration rules.